Effect of stripe domain structure orientation on secondary electron yield - Melnichuk, I.A.; Vasko, E.I.; Melnychuk, P.I. (Functional Materials, 2004)
Spatial and angular distributions of secondary electrons emitted from a uniaxial Co film surface with magnetization normal to the surface have been calculated. The electron energy has been chosen within 2 to 5 eV range (the main maximum of the energy spectrum) and at 100 eV (Auger electrons). It has been shown that the regular stripe domain structure must result in an anisotropic spatial distribution of electrons escaped from the surface and reduced secondary electron yield at small escape angles. This phenomenon is similar to the escape blocking effect at the interaction of accelerated particles with single crystals.